Akibat Hukum Apabila Pejabat Tata Usaha Negara Tidak Melaksanakan Putusan Pengadilan Tata Usaha Negara - Agus Sujiono; Dezonda Rosiana Pattipawae; Ronny Soplantila (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The weak implementation of the PTUN decision is due to the absence of an executorial institution and the force to force the implementation of the PTUN decision so that the implementation of the PTUN decision depends on the awareness and initiative of the State Administration Official. Execution of court decisions is the implementation of court decisions by or with the assistance of external parties from the parties. Matters related to execution are the cancellation of the Decree followed by rehabilitation, administrative sanctions and execution of a decision to pay a sum of money.Purposes of the Research: The purpose of this research is to analyze and discuss the forms of decisions of the State Administrative Court and the legal consequences if the State Administrative Officials do not carry out the execution of the decisions of the State Administrative Court. The writing method used is normative legal research using a statutory approach and the concept of legal analysis.Methods of the Research: This method using normative legal research methods, namely research conducted by studying literature or literature study related to the problems at hand.Results of the Research: The research results show that officials who do not carry out the obligations ordered in the decision of the State Administrative Court which have permanent legal force (inkracht van gewijsde) are subject to moderate administrative sanctions which include: a) forced payment and / or compensation; b) temporary dismissal by obtaining office rights; or c) temporary dismissal without obtaining office rights. Article 11 of Government Regulation Number 48 of 2016 concerning Procedures for Imposing Administrative Sanctions to Government Officials determines that the imposition of minor administrative sanctions is carried out directly by superior officials, while the imposition of moderate and / or severe administrative sanctions is carried out through an internal inspection mechanism. Regarding officials who are authorized to impose administrative sanctions regulated in Article 12 of Government Regulation Number 48 of 2016 concerning Procedures for Imposing Administrative Sanctions to Government Officials.